Keluarga Sakinah Dalam Kajian Hukum Islam - Asman Asman (Hukum Keluarga Islam IAIN LANGSA, 2020)
Households in the modern era experience many challenges and problems, so that many households in their journey end up in a messy household. Husbands or wives and even children no longer feel comfortable in the house, so each of them looks for pleasure and an antidote for the anxiety he faces. From this background, the writer wants to explain scientifically about the sakinah family in the study of Islamic law. This research is a literature study by taking sources from books, journals and other literature that support this research. The findings of this study explain that in theory the Sakinah family is different from its practice in society. The application of the sakinah family can be grouped into three groups, First, to obey religious advice, Second, to create a sakinah family, Third, to develop Islamic da'wah.